Contribuição de silício e micorrizas arbusculares para atenuação da toxidez por cádmio em Mimosa caesalpiniaefolia Benth. - Andrade, José Lucas Sousa de (2023)
Cadmium (Cd) is a non-essential metal for biological processes and is notoriously known for its high environmental toxicity and bioaccumulation in tissues. Soil contamination by heavy metals (PM) such as Cd is considered a global problem. Arbuscular mycorrhizal fungi (AMF) establish a mutualistic association with more than 80% of terrestrial plants and play a fundamental role in improving the absorption of essential and beneficial elements, such as phosphorus (P) and silicon (Si). Particularly, this function proves to be crucial in soils contaminated with PM. Si is an abundant element in the Earth's crust and, although it is not classified as a nutrient, its importance is highlighted due to its role in strengthening plants against environmental stresses, such as those caused by PM. Our hypothesis is that plants inoculated with AMF enhance Si absorption, resulting in a system with lower toxicity and greater tolerance for Mimosa caesalpiniaefolia Benth. in soil contaminated with Cd. Thus, we aimed to evaluate the effect of Si levels and inoculation with AMF on the initial growth and tolerance of the plant growing in soil contaminated by Cd. The test was conducted in a greenhouse at the Department of Soil Sciences of the University Federal do Ceará (UFC), Campus Pici, Fortaleza, Ceará, Brazil. The soil was distributed in pots with a capacity of 2 L. Each pot received 2 kg of soil. Soil contamination was carried out by adding Cd at a concentration of 25 mg kg-1 of soil. After the start of the Cd incubation in the soil, the addition of Si began according to the pre-established concentrations: 0 mg kg-1, 150 mg kg-1, 225 mg kg-1 and 300 mg kg-1. The species M. caesalpiniaefolia inoculated and not inoculated with Rhizoglomus clarum was used. The experimental design was completely randomized, in a 2x4 factorial scheme. Inoculation with AMF at a level of 300 mg of Si per kg of soil promoted a significant increase in yield quality variables. Microbiological variables were significantly influenced by the levels of Si applied to the soil and by inoculation with AMF. Lower Cd levels in the soil were found in treatments inoculated with AMF, and at Si levels of 225 mg kg-1 and 300 mg kg-1, with no significant interaction between the factors, being independent of each other. Lower Cd levels in the shoot were observed when there was inoculation with AMF and in conjunction with the addition of Si at all levels applied to the soil. Inoculation of M. caesalpiniaefolia with AMF, combined with application of Si, in particular at levels of 225 mg kg-1 and 300 mg Si per kg-1, mitigated Cd-induced toxicity and maximized plant growth. The interaction between AMF and Si in plants with phytostabilizing characteristics may be a promising strategy for the rehabilitation of Cd-contaminated soils.